Severe dengue in a puerperal. A case report - Maguiña Vargas , Ciro (2024)
Dengue fever is an endemic disease worldwide. When pregnant are affected, it carries a severe risk for the mother and the fetus. We present a case of a 36-year-old primigravid with 39 weeks gestation with no past medical history who was admitted to a private center in labor. She had a self-limited febrile illness two days before. She had an abnormal labor with a prolonged latent phase, uterine atony, and significant bleeding refractory to usual treatment, needing a hysterectomy. She presented severe eclampsia, oliguria, and hypovolemic shock in the immediate postpartum period, requiring admission to the ICU. Dengue was suspected due to persistent thrombocytopenia and negative procalcitonin. A positive NS1 antigen and IgM confirmed the diagnosis. The patient developed hepatomegaly and polyserositis but was discharged in good condition.